Innovative technologies for next generation access development - Kostadinova, Stela; Dimova, Rozalina (Yearbook Telecommunications, 2014)
The paper analyzes the technologies able to meet the current requirements for the provision of broadband telecommunications services in fixed access networks. The basic principles and evolutionary aspects for the development of modern access networks are examined. The structural organization of optical access networks is analyzed. NGA network technologies have been analysed and options to upgrade the existing networks are proposed.